You can cross the massacre on foot - Prestol Castillo, Freddy (Latin America in translation/en traducción/em tradução., 2019)
In 1937 tens of thousands of Haitians living in the Dominican Republic were slaughtered by Dominican troops wielding machetes and knives. Dominican writer and lawyer Freddy Prestol Castillo worked on the Haiti-Dominican Republic border during the massacre, known as "The Cutting," and documented the atrocities in real time in You Can Cross the Massacre on Foot. Written in 1937, published in Spanish in 1973, and appearing here in English for the first time, Prestol Castillo's novel is one of the few works that details the massacre's scale and scope. Conveying the horror of witnessing such inhumane violence firsthand, it is both an attempt to come to terms with personal and collective guilt and a search to understand how people can be driven to indiscriminately kill their neighbors.--